SAÚDE DOS LÍDERES RELIGIOSOS: A VOCAÇÃO EM SINTONIA COM A SAÚDE PESSOAL. UM OLHAR DE CUIDADOS SOBRE A SAÚDE DOS LÍDERES RELIGIOSOS NO CONTEXTO ATUAL - Rocca, Mauricio Carlos (2011)
This research occurs in the area of Religious Praxis and Society and concerns religious leader s health in the present-day, taking a care look at this group, in order to live their vocation in relation to their personal health, performing their vocation in secure health level. So, in the first chapter the health concept is developed through the history, to deal with at medical, theological, philosophical and psychological sphere, doing an evaluation of health s vision change with the society development until the present days. In the second chapter, from the concept of vocation on, establishes a link between health s conservation like vocation s conservation. At last, the third chapter deals with the care about religious leaders, proposing elements to improve spiritual, emotional and physical health of these leaders, in a way that their vocational work will be carried out in a full and integral way, comprising the religion leader in all his complexity.